Conjunctures and Continuities in Southeast Asian Politics (Book collections on Project MUSE., 2013)
In their evolution of political structures and life, countries often undergo significant conjunctures, major events that reorder political structures and norms. The examination of such conjunctures offers an important methodological framework to uncover and document changes that have significantly altered the political template of a country. This collection of case studies examines the critical conjunctures that have affected the countries of Southeast Asia in recent decades. Each chapter traces the antecedent conditions prior to the event, describes the changes brought about by the conjuncture, and details the lasting legacy.